2000
DOI: 10.1159/000016626
|View full text |Cite
|
Sign up to set email alerts
|

Site–Specific Oral Colonization of Mutans Streptococci Detected by Arbitrarily Primed PCR Fingerprinting

Abstract: The clonal diversity and colonization pattern of mutans streptococci within an individual were studied by using a total of 50 tooth site samples obtained from seven 3– to 7–year–old children. Five children contributed saliva samples. From the 7 subjects, 90, 74, 81, 53, 83, 103, and 114 isolates (a total of 598) representing Streptococcus mutans and Streptococcus sobrinus were included for arbitrarily primed polymerase chain reaction (AP–PCR) fingerprinting. The children harbored one to four different AP–PCR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 19 publications
1
45
2
4
Order By: Relevance
“…Elucidating the population structure of commensal bacteria requires that a significant number of isolates be collected from each site and at each visit if the full diversity of genotypes is to be revealed (1). Indeed, Hohwy et al (23) determined that, in their study, clonal diversity was likely underestimated when less than 15 isolates per subject were examined, and Gronoos and Alaluusua (20) reported that the number of genotypes of mutans streptococci that they detected was directly related to the number of isolates collected from each subject. Therefore, as much of the published data result from examination of small numbers of isolates, diversity in other species of commensal oral bacteria probably has been underestimated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Elucidating the population structure of commensal bacteria requires that a significant number of isolates be collected from each site and at each visit if the full diversity of genotypes is to be revealed (1). Indeed, Hohwy et al (23) determined that, in their study, clonal diversity was likely underestimated when less than 15 isolates per subject were examined, and Gronoos and Alaluusua (20) reported that the number of genotypes of mutans streptococci that they detected was directly related to the number of isolates collected from each subject. Therefore, as much of the published data result from examination of small numbers of isolates, diversity in other species of commensal oral bacteria probably has been underestimated.…”
Section: Discussionmentioning
confidence: 94%
“…Among the viridans streptococci, S. oralis which, genetically, is extremely closely related to S. mitis (24) also appears to be highly diverse (3). In contrast, the diversity of S. sanguinis (31) and the mutans streptococi (S. mutans and S. sobrinus) appears to be limited (1,5,20,28,34,38). Among gram-negative commensal oral bacteria, studies of Eikenella corrodens (7,8,18), Fusobacterium nucleatum (19,42), and Prevotella melaninogenica (27) show that individuals may harbor multiple genotypes whereas, in contrast, colonization with Porphyromonas gingivalis (43) and Actinobacillus actinomycetemcomitans (13,21) appears to be monoclonal.…”
Section: Discussionmentioning
confidence: 99%
“…They also found evidence of intra-family transmission, and this was extended by others using RFLP to follow transmission from mothers to their infants and to monitor the stability of S. mutans in individual mouths (Li & Caufield, 1995). Other techniques based on the variation in DNA sequence, including ribotyping (Alaluusua et al, 1994) and arbitrarily primed PCR (Gronroos & Alaluusua, 2000), have been used to monitor the populations of S. mutans. While all these methods indicate the existence of extensive sequence variation, they paradoxically imply a stability of genotype within an individual host.…”
Section: Introductionmentioning
confidence: 96%
“…Lower percentage of MS in the sample from the teeth with GIC retained brackets than in the sample from the teeth with CR-retained brackets had been identified by Ortendahl et al (28). Grönroos and Alaluusua (29) reported that the distribution of arbitrarily primed (AP)-PCR types of S.mutans differed depending on tooth site, suggesting that MS clones may selectively colonize specific hard-tissue sites. This would result in unbalance between demineralization and remineralization of dental hard tissue which would lead to the formation of smooth surface caries that appear as white spot lesion.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 88%
“…Ortendahl et al (29) also suggested that after classifying high risk patients, a special regimen should to be used. Such as cements that release fluoride might be indicated like Steinberg et al (36) and Zyskind et al (37) applied.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%